Role of hypogastric artery ligation in obstetrics and gynaecology: a 20-year study at tertiary care center, Ahmedabad, western India - Prajapati, Anjali R.; Shah, Sapana R.; Vyas, Rupa C.; Parikh, Prince M.; Patel, Ishani; Dodiya, Hetal N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hypogastric artery ligation (HAL) was first introduced by the end of the 19th century to control intractable haemorrhage from the uterus of women with advanced cervical cancer. Bilateral HAL is a lifesaving procedure in massive pelvic haemorrhage. Methods: This is a retrospective study of 58 cases in which HAL was performed in the obstetrics and gynecology department at tertiary care center from January 2000 to December 2020. History, operative procedure findings, immediate and late postoperative complications, morbidity and mortality data were collected and reviewed from records. Results: In this study, total of 58 women who underwent HAL s; 53 bilateral and 5 unilateral. Fifty-three women required HAL for obstetric indications, in 5 cases it was required for gynaecological indications. 20 cases (34.5%) underwent bilateral HAL for atonic PPH, 16 cases (27.6%) during obstetric hysterectomy for morbidly adherent placenta, 5 (8.6%) for colporrhexis, 2 (3.4%) for broad ligament hematoma, 1 (1.7%) for colporrhexis and left sided broad ligament hematoma, 2 cases (3.4%) for secondary PPH and 7 cases (12.1%) for the ruptured uterus. In gynecological cases 4 cases (80%) underwent after vaginal hysterectomy to control pelvic haemorrhage and 1 case (20%) underwent HAL after myomectomy. Conclusions: HAL is an important surgical procedure and should be performed to reduce blood loss when conservation of the uterus is desired. It is also useful in controlling haemorrhage after major gynaecological surgeries and secondary hemorrhage following hysterectomy.